POSITIVE COEXISTENCE AND BULLYING PREVENTION: THE CONTRIBUTIONS OF THE SUPPORT SYSTEM BETWEEN EQUALS - A STUDY BETWEEN THE SPANISH AND BRAZILIAN EXPERIENCES - Paulino Tognetta, Luciene Regina [UNESP]; Aviles Martinez, Jose Maria; Knoener, Darlene Ferraz [UNESP]; Aparecida de Matos, Ana Luiza [UNESP]; Bicudo Bomfim, Sanderli Aparecida [UNESP] (Univ Federal Sergipe, 2020)
Numerous studies have warned the urgent necessity for educational institutions to organize a systematic, planned and intentional program so that coexistence in school becomes a valuable asset. Furthermore, both studies and legislation on education emphasize the need for schools to carry out specific actions to counter and prevent violence manifestations, including bullying. This paper presents partial data of the establishment of a Support System between Equals model called Help Teams in Brazilian and Spanish schools. The sample consisted of 1,191 students from secondary schools in different cities of Sao Paulo State and several schools in Spain. The instrument used for data collection was INSEBULL, a specific questionnaire for the diagnosis of typical bullying situations. The results show that youth protagonist is one of the possible solutions to overcome bullying in the school environment.
Keywords: School coexistence; SAI (Support Systems Between Equals); Bullying; protagonist